Inverse association between positive tuberculin tests and positive allergy skin tests in children - Nur Rochmah; Dyahris Kuntartiwi; Anang Endaryanto; Aryanto Harsono (Paediatrica Indonesiana, 2009)
Background  The  association between  Mycobacterium  tuberculosisinfection  and  atopy remains controversial. Reaction to tuberculosisinfection  is  mediated  by  Th-1  immune responses whereas allergicreactions are mediated  by  Th- 2 immune response. In patients withatopic syndrome who also suffer from tuberculosis infection,  theTh-2  response will be suppressed  and  allergy manifestations willdecrease. Therefore, it  is  important to determine the appropriateallergy test and to predict outcome after completing tuberculosistreatment.Objective  To  evaluate the influence  of  a positive tuberculin teston  skin test results in diagnosing atopic disease.Methods  A cross sectional study was  conducted  in  the  pediatricallergy  outpatient  clinic, Soetomo Hospital, Surabaya, Indonesiabetween 2004  and  2007. Eighty-five patients were enrolled inthis study.  The  tuberculin test was performed  on  all patientswith allergy.  The  allergy test was carried  out  by  performing a skinscratch test.Results  There  was a weak inverse correlation between positivetuberculin tests and positive allergy skin tests in children (housedust  mite, food  and  pet  allergies).  The  correlation between apositive  tuberculin  test  and  house  dust  mite allergy test wasr:  -0.364  (P=O.OOl;  a=O.Ol).  The  correlation  between  thetuberculin  test  and  food allergies was  r:  -0.420  (P=O.OOl;a=O.Ol).  The  correlation between the tuberculin test  and  petallergies was  r:  -0.344  (P=  0.001;  a=O.Ol).Conclusions  A positive tuberculin test  is  weakly correlated withpositive allergy skin test results, suggesting  that  it  is  appropriate  todo allergy skin testing even in children with a positive tuberculintest.